2016
DOI: 10.12659/msm.897580
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-16 Alleviates Inflammatory Pain by Targeting Ras-Related Protein 23 (RAB23) and Inhibiting p38 MAPK Activation

Abstract: BackgroundThe purpose of our study was to determine the functional role of microRNA (miR)-16 in chronic inflammatory pain and to disclose its underlying molecular mechanism.Material/MethodsInflammatory pain was induced by injection of complete Freund’s adjuvant (CFA) to Wistar rats. The pWPXL-miR-16, PcDNA3.1- Ras-related protein (RAB23), and/or SB203580 were delivered intrathecally to the rats. Behavioral tests were detected at 0 h, 4 h, 1 d, 4 d, 7 d, and 14 d after CFA injection. After behavioral tests, L4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The CFA-induced inflammatory pain model is one of the commonly used animal models of chronic inflammatory pain as the mechanical allergy induced by CFA can last for quite a long time, and our experimental results showed in Fig. 1 were consistent with the previous reports [11,[20][21][22]. Some studies reported that CFA injection can significantly increase histone deacetylase HDACs expression and induce inflammatory pain, while the HDAC blockers can significantly alleviate CFAinduced inflammatory pain [23,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The CFA-induced inflammatory pain model is one of the commonly used animal models of chronic inflammatory pain as the mechanical allergy induced by CFA can last for quite a long time, and our experimental results showed in Fig. 1 were consistent with the previous reports [11,[20][21][22]. Some studies reported that CFA injection can significantly increase histone deacetylase HDACs expression and induce inflammatory pain, while the HDAC blockers can significantly alleviate CFAinduced inflammatory pain [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…They can bind to the 3′-untranslated region (3′-UTR) region of target mRNAs to regulate gene expression [8]. Recent studies showed that multiple miRNAs are involved in inflammatory pain, such as miR-451 may relieve chronic inflammatory pain through inhibiting microglia activation-mediated inflammation by targeting TLR4 [9], miRNA-219 expression level significantly reduced in CFA-induced chronic inflammation pain in mice model [10], and miR-16 involved in relief of chronic inflammatory pain by targeting RAB23 and inhibiting p38 MAPK activation [11].…”
Section: Introductionmentioning
confidence: 99%
“…19 Currently, there are two commonly used inflammatory pain models: One is CFA inflammatory pain model, which can be maintained for a long time and relatively stable. [20][21][22] The other is the BV inflammatory pain model by injection of bee venom to plantar subcutaneous site, which is applied to study the pathophysiological mechanism of persistent inflammatory pain. 23 In this study, we chose the classic CFA inflammatory pain model to study the expression characteristics of CXCR4.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a large number of miRNAs that were significantly deregulated in nasal mucosal tissues from AR patients using miRNA microarray. Among them, miR-16 was one of the most downregulated miRNAs and also reported to play different roles in inflammatory diseases (20,21). Thus, we chose miR-16 for further study.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Among the aberrantly expressed miRNAs, miR-16 was one of the top downregulated miRNAs in nasal mucosal tissues and altered expression of miR-16 has been found to play a critical role in inflammation in several types of diseases (20,21). We also measured its expression in 25 pairs of the nasal mucosal tissues among AR patients and NAR control group by qRT-PCR and observed that miR-16 was significantly decreased in AR group compared with NAR control group (Fig.…”
Section: Mir-16 Was Downregulated In Nasal Mucosal From Ar Patientsmentioning
confidence: 93%